Effect of Fear on the Interrelationships of the Domains of Destination Image - Felipe IV Pablo (ASEAN Journal on Hospitality and Tourism, 2023)
COVID-19 pandemic, which triggered fear, has affected the tourism industry globally, and Philippine tourism was not an exception. Gen Z travelers, an underexplored generation, are seen to play a key factor in tourism innovations. Further, destination image in the context of COVID-19 pandemic has not yet been widely explored. This study aims to investigate the effect of Filipino Gen Z’s COVID-19 fear on their perception of cognitive, affective, and conative image. Partial least squares structural equation modelling (PLS-SEM) revealed that Gen Z’s COVID-19 fear did not have a significant effect on destination image. Significant positive relationships among the destination image components were proven.  Affective image mediated the relationship between cognitive and conative images. The study contributes to the limited studies on Gen Z’s and their destination image perception during the pandemic. It encourages organizations and marketers to focus on Gen Z travelers to form positive destination image during the pandemic.